Efetividade da auriculoacupuntura sobre a qualidade de vida e aspectos emocionais em profissionais de enfermagem durante a pandemia do COVID-19: ensaio clínico randomizado - Bianca Bacelar de Assis (2022)
With the pandemic caused by SARS-CoV-2, the emergence and aggravation of negative impacts on the mental health of nursing professionals was noted. Thus, the creation and implementation of support programs for these professionals has become necessary. Among the effective interventions for the resolution or reduction of these emotional distresses, auricular acupuncture can be mentioned. The objective of this study was to evaluate the effectiveness of auricular acupuncture on the quality of life and emotional aspects of nursing professionals who were working in hospital environments during the COVID-19 pandemic. This is a randomized, controlled, parallel, and open clinical trial based on the guidelines of the Consolidated Standards of Reporting Trials. This study was carried out in a hospital in Belo Horizonte between January and September 2021. A total of 179 nursing professionals who presented moderate, severe, or extremely severe levels of stress, anxiety, or depression participated. The professionals were randomized into two groups, namely: those who received the treatment - the intervention group (n=88), and those who did not receive the intervention - the control group (n=91). The intervention group received five auricular acupuncture sessions, once a week. Semi-permanent needles were used and attached to the auricular pavilion. The instruments used for data collection were the following: a sociodemographic, psychosocial, and occupational classification instrument; the Depression, Anxiety, and Stress Scale-21; the Impact of Event Scale - Revised (IES-R), the World Health Organization Quality of Life-Bref, and the intervention evaluation instrument. Three assessments were performed to measure the variables, namely: the initial assessment, carried out before starting treatment; the final assessment, performed five weeks after the initial assessment; and the follow-up. The study was approved by the Research Ethics Committee of the Federal University of Minas Gerais and was registered in the Brazilian Registry of Clinical Trials - RBR-2JNX4S. The statistical analysis was performed using the Generalized Estimating Equations longitudinal model and the significance level adopted was 0.05. It was found that auricular acupuncture provided a significant difference of 11.74 points in the intervention group compared to the control group (p<0.001) in the perceived quality of life variable. In the physical, psychological, social relations, and environment domains, measured by the Whoqol-Bref, statistically significant intergroup differences were also found (p<0.005), with the best scores found in the intervention group. Furthermore, the difference was statistically significant between the groups in relation to emotional disorders where the group that received the intervention presented a reduction of 14.61 points (p<0.001) in the level of stress, 10.65 points (p<0.001) in the level of anxiety, and 10.56 points (p<0.001) in the level of depression. During the follow-up period, it was noted that in all variables a statistically significant difference (p<0.005) remained between the groups, with better scores found in the intervention group. Therefore, the possibility of implementing this therapy as a treatment option in health services, in order to promote the mental health of nursing professionals, stands out. Moreover, it is considered to be a technique of relevance for clinical practice in nursing, promoting and encouraging evidence-based practice.